Dietary pattern and telomere length in preschool children in a middle‐income country. Issue 3 (4th February 2021) - Meshkani, Seyed Elyas; Kooshki, Akram; Alahabadi, Ahmad; Lari Najafi, Moslem; Rad, Abolfazl; Riahimanesh, Forough; Miri, Mohammad
Abstract: Telomere length (TL) has been associated with lifestyle and dietary pattern. However, the available evidence on this association in children is scarce, especially in low‐ and middle‐income countries (LMICs). Therefore, this study aimed to evaluate the association of dietary pattern and leukocyte TL (LTL) in preschool children, Sabzevar, Iran (2017). This cross‐sectional study was based on 187 preschool children (aged 5 to 7) recruited from 27 kindergartens. Nutrition information including amounts of consumed dairy products, meat and processed meat products, nuts and seeds, white bread and refined grains, fruits, vegetables, simple sugars, fats and drinks was obtained through a questionnaire. Linear mixed‐effects models were fitted with polymerase chain reaction (PCR) plate ID and kindergartens as random effects to estimate the association of each food group consumption with LTL, controlled for relevant covariates. Higher consumption of dairy products and sugar was associated with shorter LTL ( β = −0.180, 95% confidence interval [CI]: −0.276, −0.085, P value <0.001 and β = −0.139, 95% CI: −0.193, −0.086, P value <0.001, respectively). An increase in consumption of fish, nuts and seeds, coloured fruits, green leafy vegetables, cruciferous vegetables and olive was significantly associated with the increase in relative LTL. The associations for the consumption of legumes, other fruits, yellow and orange vegetables, red meat, egg, white bread and refined grains, solid and liquid fats, processed meats, potato chips, carbonated drinks, tea (black) and soft drinks groups were not statistically significant. Our findings showed that there was an association between the consumption of certain food groups with LTL.